2010
DOI: 10.3727/096368910x509040
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Ocular Surface Injuries by Limbal and Mesenchymal Stem Cells Growing on Nanofiber Scaffolds

Abstract: Stem cell (SC) therapy represents a promising approach to treat a wide variety of injuries, inherited diseases, or acquired SC deficiencies. One of the major problems associated with SC therapy remains the absence of a suitable matrix for SC growth and transfer. We describe here the growth and metabolic characteristics of mouse limbal stem cells (LSCs) and mesenchymal stem cells (MSCs) growing on 3D nanofiber scaffolds fabricated from polyamide 6/12 (PA6/12). The nanofibers were prepared by the original needle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 35 publications
0
59
0
1
Order By: Relevance
“…The residual population of MSCs was characterized by a uniform spindle-shaped morphology, by the absence of CD11b + and CD45 + cells and by expression of phenotypic markers associated with murine MSCs. These purified MSCs had the ability to specifically differentiate into adipocytes and osteoblasts and effectively inhibit T-cell proliferation, as it has been described for MSCs [6,29].…”
Section: To Enrich Mscs In Cultures Of Bm-derived Cells We Performedmentioning
confidence: 66%
See 1 more Smart Citation
“…The residual population of MSCs was characterized by a uniform spindle-shaped morphology, by the absence of CD11b + and CD45 + cells and by expression of phenotypic markers associated with murine MSCs. These purified MSCs had the ability to specifically differentiate into adipocytes and osteoblasts and effectively inhibit T-cell proliferation, as it has been described for MSCs [6,29].…”
Section: To Enrich Mscs In Cultures Of Bm-derived Cells We Performedmentioning
confidence: 66%
“…Quantitative real-time polymerase chain reaction (PCR) was performed on an iCycler (BioRad, Hercules, CA) as we have previously described [28,29]. The primers used for amplification were as follows:…”
Section: Detection Of Tgf-b and Il-6 Gene Expression By Real-time Polmentioning
confidence: 99%
“…In our previous studies, 35,36 we demonstrated that nanofibers produced by needleless technology represent a convenient scaffold for cell cultivation and subsequent transfer to damaged tissue. The multilayered nanofibers studied in this work may offer a promising combination of such inherent properties of electrospun nanofibers with controlled drug release for developing suitable scaffolds for wound dressing applications.…”
mentioning
confidence: 99%
“…in the eye have shown that electrospun nanofibers can serve as a scaffold to grow and transfer limbal stem cells in the treatment of limbal stem cell deficiency (Zajicova et al, 2010). As biological discoveries identify key factors to stem cell survival and technological advances provide new biomaterials, the potential for improved treatment is dramatic.…”
Section: Stem Cells In Ophthalmology 411mentioning
confidence: 99%
“…It is possible this frill of conjunctiva possesses factors which enhance clinical outcomes of transplantation. Co-transfer of limbal stem cells with other stem cells, such as mesenchymal cells, may also lead to improved outcomes by inhibiting local inflammation and improving healing through immunosuppressive properties of these cells (Zajicova et al, 2010). Furthermore, human amniotic membrane may serve as a niche for limbal stem cells, possibly through the suppression of apoptosis and expression of certain growth factors (Tseng et al, 1998).…”
Section: Further Stem Cell Applications and New Advancesmentioning
confidence: 99%